International trade measures as an alternative to sanctions serving human rights protection in external relations - Ziemblicki, Bartosz (University of Wroclaw. Faculty of Law, Administration & Economics, 2012)
Trade sanctions aimed at protecting and promoting human rights can no longer be considered (if they ever could have been) a proper instrument to fight human rights violation in other states. There appears to be a reasonable alternative in other international trade measures, which also may be applied in accordance with the law of the World Trade Organization. Those measures can be divided into two categories: trade incentives adopted under the Enabling Clause and obligation waivers. This article seeks to explore whether either of those legal instruments has the potential to play a significant role in enhancing human rights standards worldwide in terms of their availability and effectiveness.
Keywords: prawa człowieka; handel międzynarodowy